Ultrasonic optic nerve sheath diameter as a new predictor for the mortality of patients with large hemispheric infarction - Jie Zhang; Shimeng Zhuang; Ying Zhang; Lisi An; Dongyang Li; Zhen Liu; Lijuan Wang (Scientific Reports)
Abstract Large hemispheric infarction (LHI) is a severe form of stroke with high mortality and poor outcomes. Ultrasonic optic nerve sheath diameter (ONSD) is considered an effective indicator for intracranial hypertension. Our study aimed to validate the efficiency of ultrasonic ONSD and develop a nomogram to identify LHI patients who have 90-day mortality. We recruited 419 LHI patients (training cohort, n = 202; internal validation cohort, n = 86; and external validation cohort, n = 131) from six centers. Demographic, laboratory, computed tomography, and ultrasonic data were collected. At 90 days, 41.8% of patients died. Ultrasonic ONSD (odds ratio [OR], 7.026; 95% CI, 2.638–18.708; P < 0.001), male (OR, 8.620; 95% CI, 2.962–25.092; P < 0.001), midline shift (OR, 1.207; 95% CI, 1.085–1.342; P = 0.001), and infarction volume (OR, 1.020; 95% CI, 1.012–1.028; P < 0.001) were independent predictors. In identifying LHI patients prone to 90-day mortality, the nomogram developed using these predictors showed areas under the receiver operating characteristic curve (AUC) of 0.897, 0.824, 0.833 in the training cohort, internal and external validation cohorts, respectively. Ultrasonic ONSD complement the midline shift and infarction volume to create a reliable multimodal method for monitoring prognosis in patients with LHI.